Optimization of secure communication channel over the volunteer cloud and cloud computing. (17th November 2021) - Sangwan, Anjana; Keswani, Bright; Sharma, Aakriti
Abstract: Voluntary computing initiatives aim to engage with the public and educate them about scientific and technological advancements. The goal and the science underpinning these initiatives may be learned a great deal by a volunteer who is involved with any of these volunteer computing programs. It is necessary to maintain a trust factor in order for volunteers in computing projects to not feel threatened by the usage of their sensitive data within the projects' scope. Using the findings of this study, we have elevated volunteer cloud computing to a new level by enabling more effective and secure communication between clients, allowing them to freely consume and provide resources.